Towards Sustainable Fishing: Enhancing Data Management in the Araguaia-Tocantins Basin with AI Technologies - Castanheira, Felipe; Andrade, Saullo; Loyolla, Luna; Souza, Marcela; Kuribayashi, Hugo; Sousa, Keid; Cunha, Cristiane (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
The Araguaia-Tocantins basin, essential for riverine communities due to its importance in artisanal fishing, faces a substantial lack of information, preventing the formulation of effective policies. Although the Fishery Statistics System (SIEPE) exists as a traditional information system, the proposed integration with Artificial Intelligence (AI) platforms allows the formulation of natural language queries that are converted into Structured Query Language (SQL) commands, thereby increasing the accessibility of the available data. This innovation has the potential to improve the management of artisanal fishing and create new business opportunities, focusing on sustainability and the preservation of natural resources.